At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the inequality [tex]\((x+1)(x-3)^2 > 0\)[/tex], let's follow a detailed, step-by-step approach.
### Step 1: Determine the critical points
First, find the values of [tex]\(x\)[/tex] that make either [tex]\(x+1 = 0\)[/tex] or [tex]\((x-3)^2 = 0\)[/tex]:
- [tex]\(x+1 = 0 \implies x = -1\)[/tex]
- [tex]\((x-3)^2 = 0 \implies x = 3\)[/tex]
These are the critical points: [tex]\(x = -1\)[/tex] and [tex]\(x = 3\)[/tex].
### Step 2: Analyze the intervals around the critical points
The critical points divide the number line into three intervals. We need to test the sign of the expression [tex]\((x+1)(x-3)^2\)[/tex] in each of these intervals:
1. [tex]\(x < -1\)[/tex]
2. [tex]\(-1 < x < 3\)[/tex]
3. [tex]\(x > 3\)[/tex]
### Step 3: Test each interval
Choose a test point in each interval and substitute it into the inequality [tex]\((x+1)(x-3)^2 > 0\)[/tex]:
#### Interval 1: [tex]\(x < -1\)[/tex]
Let's choose [tex]\(x = -2\)[/tex]:
[tex]\[ (x+1)(x-3)^2 = (-2+1)(-2-3)^2 = (-1)(-5)^2 = (-1)(25) = -25 \][/tex]
Since [tex]\(-25 < 0\)[/tex], [tex]\((x+1)(x-3)^2 < 0\)[/tex] in this interval.
#### Interval 2: [tex]\(-1 < x < 3\)[/tex]
Let's choose [tex]\(x = 0\)[/tex]:
[tex]\[ (x+1)(x-3)^2 = (0+1)(0-3)^2 = (1)(-3)^2 = (1)(9) = 9 \][/tex]
Since [tex]\(9 > 0\)[/tex], [tex]\((x+1)(x-3)^2 > 0\)[/tex] in this interval.
#### Interval 3: [tex]\(x > 3\)[/tex]
Let's choose [tex]\(x = 4\)[/tex]:
[tex]\[ (x+1)(x-3)^2 = (4+1)(4-3)^2 = (5)(1)^2 = (5)(1) = 5 \][/tex]
Since [tex]\(5 > 0\)[/tex], [tex]\((x+1)(x-3)^2 > 0\)[/tex] in this interval.
### Step 4: Checking the critical points
- At [tex]\(x = -1\)[/tex]:
[tex]\[(x+1)(x-3)^2 = (0)(4) = 0\][/tex]
- At [tex]\(x = 3\)[/tex]:
[tex]\[(x+1)(x-3)^2 = (4)(0) = 0\][/tex]
So, in these intervals, the equality holds, not the inequality.
### Step 5: Combine the results
[tex]\((x+1)(x-3)^2 > 0\)[/tex] holds for:
1. [tex]\( -1 < x < 3 \)[/tex]
2. [tex]\( x > 3 \)[/tex]
Therefore, the solution to the inequality [tex]\((x+1)(x-3)^2 > 0\)[/tex] is:
[tex]\[ x > -1 \text{ and } x \neq 3 \][/tex]
In interval notation, this is:
[tex]\[ (-1, 3) \cup (3, \infty) \][/tex]
### Step 1: Determine the critical points
First, find the values of [tex]\(x\)[/tex] that make either [tex]\(x+1 = 0\)[/tex] or [tex]\((x-3)^2 = 0\)[/tex]:
- [tex]\(x+1 = 0 \implies x = -1\)[/tex]
- [tex]\((x-3)^2 = 0 \implies x = 3\)[/tex]
These are the critical points: [tex]\(x = -1\)[/tex] and [tex]\(x = 3\)[/tex].
### Step 2: Analyze the intervals around the critical points
The critical points divide the number line into three intervals. We need to test the sign of the expression [tex]\((x+1)(x-3)^2\)[/tex] in each of these intervals:
1. [tex]\(x < -1\)[/tex]
2. [tex]\(-1 < x < 3\)[/tex]
3. [tex]\(x > 3\)[/tex]
### Step 3: Test each interval
Choose a test point in each interval and substitute it into the inequality [tex]\((x+1)(x-3)^2 > 0\)[/tex]:
#### Interval 1: [tex]\(x < -1\)[/tex]
Let's choose [tex]\(x = -2\)[/tex]:
[tex]\[ (x+1)(x-3)^2 = (-2+1)(-2-3)^2 = (-1)(-5)^2 = (-1)(25) = -25 \][/tex]
Since [tex]\(-25 < 0\)[/tex], [tex]\((x+1)(x-3)^2 < 0\)[/tex] in this interval.
#### Interval 2: [tex]\(-1 < x < 3\)[/tex]
Let's choose [tex]\(x = 0\)[/tex]:
[tex]\[ (x+1)(x-3)^2 = (0+1)(0-3)^2 = (1)(-3)^2 = (1)(9) = 9 \][/tex]
Since [tex]\(9 > 0\)[/tex], [tex]\((x+1)(x-3)^2 > 0\)[/tex] in this interval.
#### Interval 3: [tex]\(x > 3\)[/tex]
Let's choose [tex]\(x = 4\)[/tex]:
[tex]\[ (x+1)(x-3)^2 = (4+1)(4-3)^2 = (5)(1)^2 = (5)(1) = 5 \][/tex]
Since [tex]\(5 > 0\)[/tex], [tex]\((x+1)(x-3)^2 > 0\)[/tex] in this interval.
### Step 4: Checking the critical points
- At [tex]\(x = -1\)[/tex]:
[tex]\[(x+1)(x-3)^2 = (0)(4) = 0\][/tex]
- At [tex]\(x = 3\)[/tex]:
[tex]\[(x+1)(x-3)^2 = (4)(0) = 0\][/tex]
So, in these intervals, the equality holds, not the inequality.
### Step 5: Combine the results
[tex]\((x+1)(x-3)^2 > 0\)[/tex] holds for:
1. [tex]\( -1 < x < 3 \)[/tex]
2. [tex]\( x > 3 \)[/tex]
Therefore, the solution to the inequality [tex]\((x+1)(x-3)^2 > 0\)[/tex] is:
[tex]\[ x > -1 \text{ and } x \neq 3 \][/tex]
In interval notation, this is:
[tex]\[ (-1, 3) \cup (3, \infty) \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.